(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2009)
This paper deals with the regional stratigraphy around the Alps-Apennines junction during late Eocene-Miocene. The basin-fill architecture and its relation to changes in structural style were deciphered through the integration of subsurface and outcrop data on the basis of seismic- and sequence-stratigraphy principles, respectively. During late Eocene-Oligocene, the study area hosted a mosaic of partially interconnected sub-basins, and the Torino Hill area marked the junction towards the western apex of the Southern Alps foredeep (Gonfolite Basin). Since the latest Oligocene, the uplift of the north-verging Monferrato arc provided the separation from the adjacent Gonfolite Basin and the Tertiary Piedmont Basin behaved as a larger and more regularly subsiding thrust-top basin. The upper Eocene-Miocene successions record a long-term, major transgressive-regressive cycle, consisting of seven large-scale unconformity-bounded stratigraphic units, whose stacking pattern was controlled by changes in the rate of tectonic subsidence and whose boundaries were generated by basin-modification phases. During the Oligocene-lower Miocene deepening-upward sequence set, the marginal marine systems show a marked diachronism associated with the SW-ward change of coastal onlap, punctuated by drowning-platform unconformities generated in relation to basinward tilting and high-angle synsedimentary faults. The maximum transgression coincides with the late Burdigalian tectonic space creation phase, when a basinwide, highly efficient turbidite system was deposited. The middle-upper Miocene progradation, punctuated by forced regression pulses, was driven by the inversion and uplift of the southern basin margin, so that a northward shift and progressive narrowing of the turbidite depocentre occurred.